Fabrication and electrical characteristics of nano black phosphorus thin film transistor - Wang Lie-long (Functional Materials, 2016)
This text introduced a method to fabricate black phosphorus(BP) nanosheet field effect transistor(FET). The X ray diffraction analysis, scanning electron microscopy, and FET performance of the black phosphorus products were analyzed, and the output characteristic curves and the transfer characteristic curves were obtained. When BP's thickness was 14nm, the hole mobility was 244 cm2/Vs and on/off ratio was ~10³. The result shows that black phosphorus nanosheet field effect transistor has good on/off ratio and hole mobility. It will lay an important foundation for future optoelectronic devices as an alternative material.